Cancer : principles & practice of oncology. - DeVita, Vincent T., Jr., 1935-; Lawrence, Theodore S.; Rosenberg, Steven A. (Wolters Kluwer, 2021)
"This title will help you understand and apply the scientific advances that are revolutionizing cancer research and practice with Cancer: Principles and Practice of Oncology: Primer of the Molecular Biology of Cancer. Derived from DeVita, Hellman, and Rosenberg's Cancer: Principles and Practice of Oncology - widely hailed as the definitive clinical reference in oncology - the third edition of this popular Primer focuses on the molecular biology information that is of critical importance to research scientists and clinical oncologists alike. Get up-to-date, dependable coverage of every important frontier in aspect of the molecular biology of cancer with contributions from a noteworthy roster of leading scientists and clinicians. See how molecular biology advances are impacting clinical practice with separate chapters on each of the 19 most common cancer types. Navigate the challenges and ethical dilemmas of cancer genetics with a thorough section chapters on genetic counseling and genetic testing"--